COVID-19 Related Stress and Mental Health Outcomes 1 Year After the Peak of the Pandemic Outbreak in China: the Mediating Effect of Resilience and Social Support - Hu, Jingchu; Huang, Yiting; Liu, Jiayu; Zheng, Zhiying; Xu, Xiuhua; Zhou, Yunfei; Wang, Jianhong (Frontiers in Psychiatry, 2022)
Background: COVID-19 outbreak have a long-term negative impact on mental health. Meanwhile, it may also provide opportunities for a positive outcome (e.g., post-traumatic growth). Resilience and social support could serve as psychological resources to protect individuals against the detrimental effects of the COVID-19 crisis and enable people to develop positive changes during challenging times. Objective: By testing the roles of resilience and social support in the relationship between COVID-19 related stress and negative mental health outcomes (depression and anxiety), as well as the relationship between COVID-19 related stress and positive mental health outcomes (post-traumatic growth, PTG), this study aimed to investigate the psychological mechanisms involved in different mental health outcomes induced by COVID-19. Methods: An online survey was conducted one year after the peak of the COVID-19 outbreak (from April to August 2021) in China. The questionnaire includes demographic questionnaires and six scales: the Impact of Event Scale-Revised for COVID-19 (IES-RC), the 10-item Connor-Davidson Resilience Scale (CD-RISC-10), the Perceived Social Support Scale (PSSS), the Center for Epidemiological Studies Depression Scale (CES-D), the Generalized Anxiety Disorder scale (GAD-7) and the Posttraumatic Growth Inventory (PTGI). The structural equation model was used to evaluate the relations and mechanisms between COVID-19 related stress and resilience, social support in depression, anxiety, and PTG. Results: A total of 771 Chinese subjects completed the questionnaire, were 416 (54%) female, 66 (8.6%) were > 50 years old. COVID-19 related stress, resilience, and social support were associated with mental health outcomes (depression, anxiety, and PTG). Under SEM analysis, resilience mediated the effects of COVID-19 related stress on depression and post-traumatic growth. Social support mediated the impacts of COVID-19 related stress on post-traumatic growth, depression, and anxiety. The path coefficients of the mediation effects are statistically significant (all P < 0.05). Conclusions: The current findings suggest that COVID-19 related stress has a double-edged effect on mental health. Depression, anxiety, and PTG coexist in Chinese individuals one year after the peak of the pandemic. Resilience and social support served as important protective factors of mental health, safeguard people from the negative mental health outcomes of the COVID-19, and promote PTG.